2006
DOI: 10.1152/ajpcell.00199.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine stimulation of pregnancy-associated plasma protein A expression in human coronary artery smooth muscle cells: inhibition by resveratrol

Abstract: Through specific cleavage of proteins that bind and inhibit insulin-like growth factor-I (IGF-I), pregnancy-associated plasma protein-A (PAPP-A) enhances local IGF-I availability, and, consequently, receptor activation. PAPP-A expression is increased in experimental models of vascular injury and in human atherosclerotic plaque; however, little is known about the regulation of PAPP-A gene expression in vascular cells. In this study, we tested the hypothesis that proinflammatory cytokines involved in the vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 44 publications
4
60
0
2
Order By: Relevance
“…The data reported in this study are in agreement with the idea that free IGF-I is increased at lung levels (ELF values) in affected infants, further confirmed by decreased PAPP-A levels, which are always inversely correlated in the different models studied (1,10). It has already been reported that tumor necrosis factor-␣ is able to reduce IGF-I and induce the release of PAPP-A molecules (1,10).…”
Section: Epithelial Lining Fluid Levels Of Free Igf-i Papp-a and supporting
confidence: 92%
See 1 more Smart Citation
“…The data reported in this study are in agreement with the idea that free IGF-I is increased at lung levels (ELF values) in affected infants, further confirmed by decreased PAPP-A levels, which are always inversely correlated in the different models studied (1,10). It has already been reported that tumor necrosis factor-␣ is able to reduce IGF-I and induce the release of PAPP-A molecules (1,10).…”
Section: Epithelial Lining Fluid Levels Of Free Igf-i Papp-a and supporting
confidence: 92%
“…The latter is a 200-kDa metalloproteinase capable of inducing the dissociation of free IGF-I from three of the binding proteins (IGFBP-2, -4, and -5). In addition to the placenta, PAPP-A is expressed in a wide variety of reproductive and nonreproductive organs and fetal tissues, and many cells are able to produce PAPP-A, such as fibroblasts, endothelial cells, and smooth muscle cells (3,10,16,25).…”
mentioning
confidence: 99%
“…28 TNF-␣ and IL-1␤ are potent stimulators of PAPP-A gene expression in coronary artery smooth muscle cells. 29 Thus, we speculate that upregulation of PAPP-A in vascular cells by macrophage-derived cytokines is an important component of lesion development, and, in the absence of this target gene, lesion development is blunted in spite of the continued presence of macrophages and similar levels of TNF-␣ and IL-1␤ expression in aortas from KO/KO and ApoE KO mice. Indeed, the percentage of lesion staining for macrophages was higher in KO/KO compared with ApoE KO mice, whereas the absolute area of macrophage staining was approximately the same in the 2 groups.…”
Section: Discussionmentioning
confidence: 81%
“…PAPP-A expression is stimulated by TNF-α and interleukin 1 beta (IL1-β ) (52 -54) and this cytokine induced expression can be inhibited by antioxidants N-acetyl cysteine (53) or polyphenol resveratrol (54) . Resveratrol is found in the skin of grapes and in red wine which might contribute to the explanation of the French paradox of benefi cial effect of consumption of red wine on reduced cardiovascular risk.…”
Section: Pharmacological Infl Uence Of Papp-a Expression and Circulatmentioning
confidence: 99%